The Drug Dependants (Treatment And Rehabilitation) Act 1983 - Kamariah, Mimi A.M. (Journal of Malaysian and Comparative Law, 2019)
This Act provides "for the treatment and rehabilitation of drugs dependants and for matters connected therein". It repeals the whole Part VA of the Dangerious Drugs Act 1952 (DDA) and various definitions of terms which were relevant only to Part VA. In doing so, it seeks to provide for a more comprehensive statute dealing only with the treatment and rehabilitation of drugs dependants. Notwithstanding this repeal, Part VA still applies if any person has been taken into custody, or has been or is being dealt with in any manner by any court, Magistrate, Social Welfare Officer, Board of Visitors, or any other officer or authority before the commencement of the DDTRA. The only qualification is that certain references to officers and authorities now refer to corresponding officers and authorities under the DDTRA.